Sustaining the Roles of Non-Timber Forest Products in Rural Poverty-Reduction and Household Food Security in Nigeria (2006)
"Forest outputs are broadly classified into timber and Non-Timber Forest Products (NTFPs). While the timber component has been widely acknowledged as great contributor to both national and local economies, the equally important non-timber component had received little attention from social scientists and development planners until very recently. Non-timber forest products are all those goods and services of biological origin obtained from forests or associated ecosystems, which contribute directly or indirectly to human welfare. The non-timber forest products contribute immensely to household food security and income generation in Nigeria. Hence they play a significant role in rural poverty reduction. In Nigeria poverty, incidence had increased from 27.2% in 1980 to 65.6% in 1996. This disturbing trend has prompted the federal government and international agencies to formulate various programs aimed at reducing the poverty incidence in the country. Many of such programs have however failed to achieve the desired objectives because they failed to understand the intimate relationship between the rural people and their immediate environment. The poor depends largely on land and various plants and animal resources obtainable from it. The closely interwoven relationship between the people and their biotic environment should be carefully understood and adjusted in such a way that the ecosystem balance is sustained. This study examines the significant roles played by non-timber forest products in rural livelihood sustenance in Nigeria. Various strategies for sustainable production and utilization of the products are discussed. "